Effektivitas Metode Edukasi Brainstrorming untuk Meningkatkan Pemahaman Kasus di Lahan Praktik pada Mahasiswa Profesi Ners - NH Noeraini; Yeni Eliyanti; Dita Amita (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
This study aims to determine the effectiveness of learning brainstorming methods on the ability to understand cases in the practice area. The research design used was nonequivalent control group design consisting of experimental groups, namely the treatment of brainstorming methods and the control group with conventional methods, then all groups assessed the level of understanding of the case at the time of pre and post experiment. The results of this study, the intervention group was seen to be more meaningful with a p value of 0,000 compared to the control group. Conclusion, brainstorming education is more effective to be applied to improve the understanding of cases in Nurse profession students in the practice field. Keywords: Brainstorming, Education, Understanding